2003
DOI: 10.1051/kmae:2003021
|View full text |Cite
|
Sign up to set email alerts
|

REPRODUCTION DE LA TRUITE (Salmo trutta L.) DANS LETORRENT DE CHEVENNE, HAUTE-SAVOIE.UN FONCTIONNEMENT ORIGINAL ?

Abstract: RÉSUMÉLa reproduction d'une population de truite (Salmo trutta L.) de forme essentiellement méditerranéenne est décrite dans le ruisseau du Chevenne, un torrent à forte pente (10 %) entrecoupé d'obstacles et limité en substrat de frai, situé dans les Alpes savoyardes. Les reproducteurs (résidents du torrent ou migrants issus du cours principal) diffèrent en taille et sexe-ratio. La majorité (58 %) des femelles migrantes entrent dans l'affluent déjà ovulées. Il existe une fort gradient décroissant aval-amont da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 29 publications
5
26
0
1
Order By: Relevance
“…Admittedly, the highest daily mean in December recorded during our observation period did not exceed 33.05 m 3 AEs )1 (December 2002) and we assume that higher discharges in the range of annual highs (57 m 3 AEs )1 ) cause mortality and reduce the YOY-class strength drastically (Nelson 1986). The extended spawning period can be an adaptation to the unpredictable and harsh flow conditions, as supported by Gortázar et al (2007) and Champigneulle et al (2003) or the consequence of introgression of foreign strains as a result of stocking. The extended spawning period can be an adaptation to the unpredictable and harsh flow conditions, as supported by Gortázar et al (2007) and Champigneulle et al (2003) or the consequence of introgression of foreign strains as a result of stocking.…”
Section: Discussionsupporting
confidence: 89%
“…Admittedly, the highest daily mean in December recorded during our observation period did not exceed 33.05 m 3 AEs )1 (December 2002) and we assume that higher discharges in the range of annual highs (57 m 3 AEs )1 ) cause mortality and reduce the YOY-class strength drastically (Nelson 1986). The extended spawning period can be an adaptation to the unpredictable and harsh flow conditions, as supported by Gortázar et al (2007) and Champigneulle et al (2003) or the consequence of introgression of foreign strains as a result of stocking. The extended spawning period can be an adaptation to the unpredictable and harsh flow conditions, as supported by Gortázar et al (2007) and Champigneulle et al (2003) or the consequence of introgression of foreign strains as a result of stocking.…”
Section: Discussionsupporting
confidence: 89%
“…Distinct spawning behaviours related to either the timing of spawning and ⁄ or use of specific habitats that influence the duration of the incubation period have already been reported in other salmonid species (Hansen, 1975;Hendry, Hensleigh & Reisenbichler, 1998;Beer & Anderson, 2001). One can also speculate that the co-existence of these distinct tactics that result in a wider range of hatching ⁄ emergence dates may enhance population stability, as has been suggested for brown trout (Salmo trutta, L.) in mountain streams (Hansen, 1975;Champigneulle, Largiader & Caudron, 2003). the selection of cold-regime ⁄ downwelling sites versus warm-regime ⁄ upwelling sites) does not confer an advantage in fitness, assuming both tactics have been maintained since brook trout colonised the Canadian Shield c. 10 000 years ago (Mandrak & Crossman, 1992).…”
Section: Contrasting Thermal Regimes In Incubation Microhabitats: Dismentioning
confidence: 63%
“…Furthermore, the water temperature in the Castril was always within the brown trout 'growth zone', as defined by Elliott (1994). The highest densities reported by Champigneulle et al (2003) in a highly fragmented mountain stream (6.3 reddsAE100 m )2 ) greatly exceeded the Castril redd densities. The highest redd density in our study (reach 3) was slightly lower than that reported by Rubin et al (2004) for sea trout (1.56 -reddsAE100 m )2 ).…”
Section: Influence Of Stream Flow and Water Temperaturementioning
confidence: 77%
“…The Mediterranean climate of this region shapes the flow regime, making its interannual variations highly unpredictable: peak flows may occur at any time during the spawning season. Champigneulle et al (2003) already suggested that spatio-temporal dispersion of reproduction is likely to impede population extinction. It is known that a catastrophic event (like a spate or a drought) may weaken the year's recruitment if it happens at the critical stages of the life cycle (e.g., Frost & Brown 1967;Anderson 1983;Spina 2001;Cattanéo et al 2002) and thus, it might put the population at risk.…”
Section: Spawning Periodmentioning
confidence: 99%
See 1 more Smart Citation